Deformation of shuttlecock skirt - Zhang, Lu Yin (Nanyang Technological University, 2023)
The origins of badminton can be traced back to ancient India, where a similar game called "Poona" was played. The game involved hitting a shuttlecock with the hand, and it was played by both children and adults. British officers stationed in India in the mid-19th century were introduced to the game, and they brought it back to England. The game was initially called "battledore and shuttlecock" and was played with small rackets called battledores and a shuttlecock made of cork and feathers. The game of badminton quickly gained popularity in England and soon spread to other parts of the world. The first badminton club was formed in England in 1877, and the first All England Badminton Championships were held in 1899. The sport also gained popularity in other European countries, as well as in India and other parts of Asia. In the 1930s, badminton was standardized, and the International Badminton Federation was formed to oversee the game's rules and regulations. Today, badminton is a popular sport played by millions of people around the world. It is played both recreationally and competitively, with professional players competing in international tournaments such as the Olympic Games, the World Championships, and the Thomas and Uber Cups. There are two types of shuttlecocks, synthetic, and feather shuttlecocks. The synthetic shuttlecock was invented in the 1940s as a more durable and consistent alternative to feather shuttlecocks. Synthetic shuttlecocks are the most commonly used type of shuttlecock in the game of badminton, particularly at the amateur and recreational levels. They are less expensive than feather shuttlecocks and do not require special storage or handling like feather shuttlecocks do. The aim of this Final Year Project (FYP) is to investigate the relationship between the deformation of a synthetic shuttlecock's skirt and its performance, as previous studies have primarily focused on feather shuttlecocks. In this experiment, 5 different synthetic shuttlecocks were tested and compared, in which some are BWF competition graded while some are not. The shuttlecocks used are listed below:  1) Yonex Mavis 10 (BWF Competition Graded) 2) Yonex Mavis 350 (BWF Competition Graded) 3) Yonex Mavis 600 (BWF Competition Graded) 4) Decathlon Perfly PSC 130 5) Decathlon Perfly PSC 900 The Badminton World Federation (BWF) carries out durability tests on badminton shuttlecocks by picking three random ones and having professional players hit them ten times to make sure they don't get permanently damaged [1]. This same method is used in my FYP with a special testing machine that simulates the hitting action of a racket. Each hit is recorded with a high-speed camera and analysed with feature recognition and motion tracking software to examine how the shuttlecock skirt changes shape. From the results, it can be concluded that there is no significance difference in terms of the average maximum deformation of the shuttlecocks’ skirt between the BWF Competition Graded and Non-BWF approved shuttlecocks, but there is a difference within the group. Among the 3 BWF Competition Graded shuttlecocks, the superior one had the least deformation and similarly for the 2 Non-BWF approved shuttlecocks. Amongst the 5 shuttlecocks, the most superior one did have the least deformation.